Konflik dan Resolusi dalam Pembagian Harta Pasca Perceraian di Tanah Pusaka Minangkabau - Agung Setiawan, M.; Zola Efendi, Hendri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This research describes a case study from Nagari Koto Tangah, Kecamatan Tilatang Kamang, where the clash between customary law and individual rights became the focal point in resolving shared assets following a divorce. The case involves an intercultural marriage—a husband of Javanese descent and a wife from Minangkabau. After years of marriage and building a house on the wife's ancestral land (Tanah Pusaka Tinggi), their marriage ended in divorce. Although the house was built together, the land, according to Minangkabau custom, could not be sold or transferred to an outsider, including the former husband. During mediation, the wife's family offered compensation to the former husband, but he found the compensation inadequate, leaving lingering dissatisfaction on his part. This study highlights the importance of understanding customary law and individual rights in intercultural marriages. Through a humanistic approach, the research illustrates how Minangkabau customary law protects Tanah Pusaka Tinggi as an integral part of the family's ancestral heritage while also revealing the limitations of legal frameworks in addressing the emotional dissatisfaction that often follows a divorce. By analyzing the perspectives of traditional leaders, religious scholars, and civil law experts, the study proposes a mediation solution that respects customary practices while addressing individual rights. In conclusion, while the conflict is formally considered resolved, the former husband's emotional dissatisfaction indicates that material compensation alone may not achieve full justice. This research recommends the use of prenuptial agreements and legal education on intercultural marriages to prevent similar conflicts in the future.